Over the Top: Canadian Red Cross Fundraising during the Second World War - Walker, Eric Keith (Université d'Ottawa / University of Ottawa, 2011)
Throughout the Second World War, the Canadian Red Cross Society (CRCS) exerted its significant influence in the field of voluntary homefront labour to provide a vast number of services for the benefit of Canadian, Commonwealth and Allied servicemen, prisoners of war, and civilians affected by the horrors of war. These wartime programs, which cost the Society over $90 000 000, were made possible through voluntary contributions of millions of dollars from Canadian citizens mainly through the yearly Red Cross national campaigns. Because of the organization’s claim to reach over cultural, ethnic, linguistic and religious lines, it benefitted from the support of various national groups within Canada. Another important group of contributors to the Red Cross structure were women who formed the backbone of the organization’s structure. Women served in nearly every capacity within the CRCS, which allowed them to gain valuable experience in a working environment outside of the home.
Keywords: Red Cross; Canada; humanitarianism; women; homefront; Second World War